Population genetics of caribou in the Alaska-Yukon border region: implications for designation of conservation units and small herd persistence ... - Mager, Karen Hibbard-Rode (Dryad, 2024)
Better knowledge of genetic relationships between the Fortymile caribou herd and its neighbors is needed for conservation decision-making in Canada. Here, we contribute the first fine-scale analysis of genetic population structure in nine contiguous caribou herds at the geographic boundaries between Barren-ground and Northern Mountain caribou, and at the Alaska-Yukon border. Using pairwise differentiation metrics, STRUCTURE, and discriminant analysis of principal components (DAPC) to analyze 15 microsatellite loci in 379 caribou, we found complex patterns of genetic differentiation. The Fortymile was the only herd assigned to more than one genetic cluster, indicative of its history as a larger herd whose range expansions and gene flow to other herds were likely important to maintaining diversity across a functioning genetic metapopulation. Some small herds (Chisana, Klaza, and White Mountains) were genetically distinct, while others (Hart River, Clear Creek, Mentasta) exhibited little differentiation from ... : Caribou whole blood, dried blood on filter paper, hair, and fecal samples were collected by the Yukon Department of Environment, Alaska Department of Fish and Game, and Bureau of Land Management. The herd identities of sampled caribou were determined by biologists in the natural resource agencies who sampled them, usually based on presence in known seasonal ranges and often confirmed with collar locations. Most samples were from adult females. See publication for detailed description of DNA extraction, PCR, genotyping, and error-checking protocols use to produce this dataset of genotypes of 379 individual caribou at 15 microsatellite loci. ...